Soil organic matter and aggregate dynamics in an Arctic ecosystem - Simpson, Rodney T., author; Moore, John C., advisor; Cafaro, Philip, 1962-, committee member; Paustian, Keith H., committee member; Six, Johan, committee member (Colorado State University. Libraries, 2010)
Warming has been linked to changes in Arctic soil carbon cycling. Cold temperatures and anoxic conditions in the Arctic diminish microbial activity. As a result mineralization rates are low and the system is nitrogen-limited, further reducing biological activity. Reducing this constraint on nutrient availability has resulted in a vegetation shift and loss of soil carbon; however, the mechanisms behind soil carbon loss are not well understood. The focus of this study was on the active mineral layer directly below the organic horizon. Soils were collected during the 2007 growing season from a long-term nutrient addition experiment in which soils had been fertilized with additional N and P since 1996 and 1989 at the Arctic LTER site at Toolik Lake, on the Alaskan North Slope. Roots were separated from the soil to estimate biomass. Soils were separated into four size classes of water-stable aggregates (Large and small macroaggregates, microaggregates, and silt+clay). Small macroaggregates were separated into three sub-fractions (coarse particulate organic matter (POM), occluded microaggregates, and silt+clay). Density floatation was used to separate light fraction (LF) organic matter from heavy fraction in small macroaggregates and microaggregates. Intra-aggregate POM (iPOM) content was determined in small macroaggregates and microaggregates. Differences in aggregate size distribution, C and N allocation, and C:N in each fraction were analyzed. Small Macroaggregates were the dominant aggregate fraction in all treatments. Mid-season declines in large macroaggregate abundance from soils with nutrient addition differed statistically from the control, though both comprised <10% of the whole soil. The ratio of free:occluded microaggregates rose over the growing season, which indicated that microaggregates occluded within small macroaggregates were released upon macroaggregate disruption. Occluded microaggregates tended to possess higher carbon and nitrogen contents than free microaggregates due to increased physical protection within the macroaggregate. As a result, the ratio of free:occluded microaggregate C:N declined over the growing season, possibly due to N-rich, formerly occluded microaggregates entering the free microaggregate pool. Nutrient addition resulted in changes in C allocation in the small aggregate LF and microaggregate iPOM to an increasingly large amount over the growing season. Nitrogen allocation responded in a similar manner, resulting in a lower C:N in the LF of soils under nutrient addition since 1989. Nutrient addition resulted in an increase in root biomass by the middle of the growing season; however by the final sampling date, root biomass declined. Nutrient addition affected aggregate size class distribution only in mid-June, which indicated that this is a dynamic period of aggregate formation and may be dependent on the microbial community and N availability. Macroaggregate turnover, as evidenced by free:occluded microaggregate abundance, occurred earlier in the growing season in soils with nutrient addition than the control. As a result, SOM formerly occluded within macroaggregates may be increasingly susceptible to decomposition by the microbial community over the growing season. The re-allocation of SOM from physically protected aggregates to light fraction with nutrient addition may result in shifts in SOM stability in these soils. The observed increases in the proportion of soil carbon as light fraction and iPOM with nutrient addition indicate a shift towards an increase in POM fractions that tend to be labile, potentially mineralizable sources of organic matter. The balance between the rates of organic matter input and decomposition may favor decomposition, resulting in a short-term loss of carbon in Arctic soil. Carbon content may stabilize in the future as its remaining stocks become increasingly processed by the microbial community. These results highlight the importance of multiple sample collection dates, which are necessary if we are to improve our understanding of factors driving SOM stabilization in Arctic soils.
Keywords: arctic ecology; soil organic matter; soil aggregates; Carbon cycle (Biogeochemistry) -- Soils -- Arctic regions; Ecological disturbances -- Arctic regions; Toolik Lake (Alaska) -- Soils -- Analysis; Soil structure -- Arctic regions